2013
DOI: 10.1080/17458080.2013.814172
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic removal of phenol under visible light irradiation on zinc phthalocyanine/mesoporous carbon nitride nanocomposites

Abstract: A series of zinc phthalocyanine/mesoporous carbon nitride (ZnPc/MCN) nanocomposites was prepared successfully by an impregnation method. The addition of ZnPc (0.05-1.5 wt%) extended the absorption of MCN to longer visible light region without affected its structure. It was found that the photocatalytic activity of the nanocomposites for phenol removal depended on the loading amount of ZnPc. The photocatalytic activity of the MCN increased as the amount of ZnPc increased to 0.05 wt%, but further increase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The peaks (100) and (002) were ascribed correspondingly to in-plane structural packing motif and graphitic stacking of aromatic segments, with respective distance-spacing values (d) of 0.677 and 0.324 nm. These values were similar to the reported values for the CN and MCN [2][3][4][5][6]. The peaks (100) and (002) confirmed the presence of the in-plane triazine units and graphitic structure of the MCN.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The peaks (100) and (002) were ascribed correspondingly to in-plane structural packing motif and graphitic stacking of aromatic segments, with respective distance-spacing values (d) of 0.677 and 0.324 nm. These values were similar to the reported values for the CN and MCN [2][3][4][5][6]. The peaks (100) and (002) confirmed the presence of the in-plane triazine units and graphitic structure of the MCN.…”
Section: Resultssupporting
confidence: 89%
“…Even though the MCN is more preferable than the CN due to its high surface area, the MCN still suffers from fast electron-hole recombination rate and weak visible-light harvesting ability. These drawbacks have limited the photocatalytic efficiency of MCN and further modifications are desired, such as by addition of dye [3], graphene [4] or graphene oxide [5].…”
Section: Introductionmentioning
confidence: 99%
“…[2,12] However,t he adsorption capacityo fc arbon materials is lowo wing to weaker adsorbent-adsorbate interactions that are ascribed to the hydrophobic nature and lack of surfacec harges. [27] In our previousr eport, [28] the synthesis of MCN with controlled morphology was successfully achieved by synthesizing the silica template under "static" conditions and then using it as at emplate to prepareMCNs with rod-shapedm orphology that showede nhanced CO 2 capacity relative to that of MCN with irregular morphology.H owever, low-temperature carbonization is needed to preserve ah igh contento fn itrogen in the carbon matrix owing to the poor thermodynamic stabilityo f nitrogen in the carbon matrix, which is also the reasonf or the amorphousC Nw all structure,t ogether with low specific surface area in MCN. [2,14,15] It has been reported that the incorporation of nitrogen atoms into the carbon matrix is ac omplex process because it is normally achieved by either post-treatmentwith ammonia at high temperature or organicfunctionalization of carbon materials with asuitable amine.…”
Section: Introductionmentioning
confidence: 99%
“…[19] MCNs are multifacetedm aterials that find applicationsi nb asic catalysis, [20] enzyme-like catalysis, [21] gas sensing, [22] CO 2 capture, [23,24] water splitting, [25] energy storage, [26] and environment applications. [27] In our previousr eport, [28] the synthesis of MCN with controlled morphology was successfully achieved by synthesizing the silica template under "static" conditions and then using it as at emplate to prepareMCNs with rod-shapedm orphology that showede nhanced CO 2 capacity relative to that of MCN with irregular morphology.H owever, low-temperature carbonization is needed to preserve ah igh contento fn itrogen in the carbon matrix owing to the poor thermodynamic stabilityo f nitrogen in the carbon matrix, which is also the reasonf or the amorphousC Nw all structure,t ogether with low specific surface area in MCN. By tuning the carbonization temperature, the nitrogen content, crystallinity,s pecific surface area, and specific PV could be optimized.H owever,n or eports are available on the effectso fc arbonization temperature on the structural and textural properties, morphology control,n itrogen contents, and basic properties of MCN with controlled morphologyf or CO 2 capture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation